Making M&A's successful - DiGeorgio, Richard (Henry Stewart Talks, 2009)
M&A activity worldwide, Most M&A's fail to deliver, Cisco a best practice company, Systems' approach to successful M&A's, Differentiators, Options for culture change, Large mergers and change culture, Accountability, Openness and dialogue, Integration manager, Transition structure, Effective communications, Non-financial measures of success
Archived at 2025/05/28